A Rare Coexistence of Retroperitoneal Pararenal Castleman's Disease with Focal Nodular Hyperplasia - Theodosios Theodosopoulos; Andreas Karakatsanis; Anneza I. Yiallourou; Fotios Nikolakopoulos; Vassiliki Psychogiou; Eleni Karvouni; Dionysios Voros (Case Reports in Surgery, 2013)
Castleman's disease is a distinct form of lymph node hyperplasia divided into a solitary and a multicentric type. The solitary type occurs most commonly in the mediastinum and is usually asymptomatic. We present a patient with Castleman's disease of the hyaline-vascular solitary type located in the retroperitoneum. The patient was a 38-year-old male, who presented to our hospital with fever. The imaging workup revealed a retroperitoneal mass, measuring 4 × 6 cm, located lateral to the aorta, inferior to the left renal artery and vein, and posterior to the left testicular vein. At workup, a solid hepatic lesion, 3 cm in diameter, located in the left lobe of the liver, segment IV, was also identified. Both lesions were surgically excised. The retroperitoneal tumor had the features of angiofollicular hyperplasia (Castleman's disease), hyaline-vascular type, whereas a diagnosis of focal nodular hyperplasia was made for the hepatic lesion. The patient is well at fourty months followup postoperatively. Surgical excision is the treatment of choice for unifocal Castleman's disease.